A multidisciplinary and integrative review of the structural genome and epigenome of Capsicum L. species - de Almeida, Breno Machado; Clarindo, Wellington Ronildo (Planta, 2025)
Main conclusion We revised and integrated the genomic and epigenomic data into a comparative Capsicum ideogram, evidencing the advances and future perspectives. Capsicum L. (Solanaceae) genome has been characterized concerning karyotype, nuclear and chromosomal genome size, genome sequencing and physical mapping. In addition, the epigenome has been investigated, showing chromosomal distribution of epimarks in histone amino acids. Genetic and epigenetic discoveries have given light to understanding the structure and organization of the Capsicum “omics”. In addition, interspecific and intraspecific similarities and diversities have been identified, characterized and compared in taxonomic and evolutive scenarios. The journey through Capsicum studies allows us to know the 2 n = 2 x = 24 and 2 n = 2 x = 26 chromosome numbers, as well as the relatively homomorphic karyotype, and the 1C chromosomal DNA content. In addition, Capsicum “omics” diversity has mainly been evidenced from the nuclear 1C value, as well as from repeatome composition and mapping. Like this, Capsicum provides several opportunities for “omics”, ecological, agronomic and conservation approaches, as well as subjects that can be used at different levels of education. In this context, we revisit and integrate Capsicum data about the genome size, karyotype, sequencing and cytogenomics, pointing out the progress and impact of this knowledge in taxonomic, evolutive and agronomic contexts. We also noticed gaps, which can be a focus of further studies. From this multidisciplinary and integrative review, we intend to show the beauty and intrigue of the Capsicum genome and epigenome, as well as the outcomes of these similarities and differences.